2016
DOI: 10.1111/bjh.13904
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intensity VEPEMB regimen compared with standard ABVD in elderly Hodgkin lymphoma patients: results from a randomized trial on behalf of the Fondazione Italiana Linfomi (FIL)

Abstract: Survival rates for elderly Hodgkin Lymphoma (HL) have not improved substantially in recent years, mainly because of a lack of prospective randomized studies, due to difficulties in enrolling patients. Between 2002 and 2006, 54 untreated HL patients, aged between 65 and 80 years and considered 'non-frail' according to a comprehensive geriatric evaluation, were enrolled into a phase III randomized trial to compare a reduced-intensity regimen (vinblastine, cyclophosphamide, procarbazine, prednisone, etoposide, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…In the SHIELD study an attempt to reduce treatment intensity was made with VEPEMB regimen (vinblastine, cyclophosphamide, procarbazine, etoposide, mitoxantrone, bleomycin), including only 2 bleomycin doses . However, a randomized trial comparing VEPEMB with ABVD showed the same treatment‐related mortality with reduced progression‐free survival (PFS) for VEPEMB regimen …”
Section: Patient's Characteristicsmentioning
confidence: 99%
“…In the SHIELD study an attempt to reduce treatment intensity was made with VEPEMB regimen (vinblastine, cyclophosphamide, procarbazine, etoposide, mitoxantrone, bleomycin), including only 2 bleomycin doses . However, a randomized trial comparing VEPEMB with ABVD showed the same treatment‐related mortality with reduced progression‐free survival (PFS) for VEPEMB regimen …”
Section: Patient's Characteristicsmentioning
confidence: 99%
“…In the aforementioned VEPEMB study, Zallio et al () used co‐morbidity according to the CIRS, the ADL index, index of Instrumental Activity of Daily Living and Geriatric Depression Scale (GDS). Patients were defined as frail and excluded from the study, if they met one or several of the following conditions: age ≥80 years, ≥3 grade 3 comorbidities or ≥1 grade 4 comorbidity according to the CIRS scale, ADL score <6 and/or geriatric syndrome.…”
Section: Frail Patientsmentioning
confidence: 99%
“…In contrast, mediastinal involvement and bulky lymphoma are less common in older compared to younger patients (Engert et al , ; Klimm et al , ). One important characteristic in older HL patients is their low tolerance to treatment due to pre‐existing comorbidities, resulting in dose reductions, therapy delays and, ultimately, excessive treatment‐related toxicity and mortality (Proctor et al , ; Böll et al , 2013a, ; Zallio et al , ; Björkholm et al , ). Remarkably this increased vulnerability towards therapy‐associated toxicity is not restricted to patients above the age of 60 years but treatment‐related toxicity and mortality is increased even at the age of 40 or 50 years compared to younger patients (Wongso et al , ; Björkholm et al , ).…”
mentioning
confidence: 99%
“…Interestingly, independent of chemotherapy regime, no patients who were ‘frail’ achieved a CR at the end of treatment (Proctor et al , ). A small randomised trial compared VEPEMB to ABVD in carefully‐selected non‐frail patients aged 65–80 years, and found the results with ABVD to be slightly better, with 5‐year PFS rates of 48% vs. 70% and OS 63% vs. 77%, although these differences were not significant owing to the small size of the study (Zallio et al , ). Similar results were seen in the RATHL trial, where the 5‐year PFS among 43 patients over 65 years was 65%, with a 5‐year OS of 83% (Johnson et al , ).…”
Section: Initial Treatment In Older Patientsmentioning
confidence: 99%